The ability to maintain postural balance by water polo players during supervised training of Polish junior national team members - Zurek, P.; Rynkiewicz, T.; Rynkiewicz, M.; Kos, H. (Studies in Physical Culture and Tourism, 2012)
Introduction. The ability to maintain one`s balance depends on a variety of coordination skills and is necessary both for performing sports and everyday activities. Aim of Study. 1. To determine the ability of water polo players from the Polish junior national team to maintain static body balance; 2. To analyze the effects of body mass on the basic ability to maintain postural balance. Hypotheses: 1. Water polo players during supervised training are characterized by a high ability to maintain postural balance; 2. The body mass of junior athletes significantly influences their ability to maintain static body balance. Material and Methods. A group of water polo players performed three tasks: a) standard - with their eyes open; b) with their eyes closed; c) with feedback. Results and Conclusions. Using visual control allowed water polo players to achieve optimal characteristics in their ability to maintain postural balance. Significant differences were observed between the center of pressure distribution area [COPA, mm2]; results of trials with open and closed eyes, as well as between the closed eyes trial and feedback trial. A significant relationship between the ability to maintain postural balance and body mass was noted during the open eyes trial. Players with a greater body mass achieved less favorable COPA characteristics during this trial.